2014
DOI: 10.1038/ismej.2013.253
|View full text |Cite|
|
Sign up to set email alerts
|

Links between plant and fungal communities across a deforestation chronosequence in the Amazon rainforest

Abstract: Understanding the interactions among microbial communities, plant communities and soil properties following deforestation could provide insights into the long-term effects of land-use change on ecosystem functions, and may help identify approaches that promote the recovery of degraded sites. We combined high-throughput sequencing of fungal rDNA and molecular barcoding of plant roots to estimate fungal and plant community composition in soil sampled across a chronosequence of deforestation. We found significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
89
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 18 publications
10
89
0
4
Order By: Relevance
“…The bacterial community shifts were more gradual and overlapping, while the fungal communities at different ages were more distinct. This agrees with previous observations that plant symbioses with fungi are more common than with bacteria (16) and that plant community composition has strong influences on the fungal community (17)(18)(19)(20), which has been shown to extend to bulk soil in the form of common mycelial networks (42,43). The specificity with vegetation may explain the distinctness of fungal communities at different chronosequence ages, as the plant community is also experiencing taxonomic shifts from being grass dominated to tree dominated during this time frame (44).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The bacterial community shifts were more gradual and overlapping, while the fungal communities at different ages were more distinct. This agrees with previous observations that plant symbioses with fungi are more common than with bacteria (16) and that plant community composition has strong influences on the fungal community (17)(18)(19)(20), which has been shown to extend to bulk soil in the form of common mycelial networks (42,43). The specificity with vegetation may explain the distinctness of fungal communities at different chronosequence ages, as the plant community is also experiencing taxonomic shifts from being grass dominated to tree dominated during this time frame (44).…”
Section: Discussionsupporting
confidence: 90%
“…While there are exceptions to these characterizations, on a broad scale, they highlight the potential for functional differences in how each group responds to ecosystem restoration. Furthermore, while both bacteria and fungi form symbiotic relationships with plants, fungal symbionts are more common, occurring in over 85% of all angiosperms (16), and fungi tend to have more specific relationships with plant species (17)(18)(19)(20). Fungi may also be more dispersal limited than bacteria due to their larger sizes (21), and priority effects can have greater influence on fungal communities (22).…”
mentioning
confidence: 99%
“…It should be noted that the latter investigation was carried out on soils of the unvegetated habitat. Because the fungal community was closely related with vegetation (Mueller et al 2014), the aboveground plant community could be an important factor that determines fungal community composition. Taxonomic compositions of fungal community in the Tibetan forest soil were also different from that in the Amazon rainforest soils dominated by Sordariomycetes and Saccharomycetes (Peay et al 2013).…”
Section: Characteristics Of Fungal Community In Typical Forest Soils mentioning
confidence: 99%
“…Forest biomes on the Tibetan Plateau suffered from harsh environmental conditions including strong UV, low temperature and low oxygen content, and the support from the underground communities was especially important in sustaining the biological diversity and ecosystem functions in a scenario of global change Bardgett and van der Putten 2014;Shen et al 2014b). Fungi are recognized as a vital component of the belowground community intimately related with plant communities in a forest (He et al 2005;Mueller et al 2014;Peay et al 2013). Soil fungi play a key role as decomposer to accelerate degradation of soil organic carbon and nitrogen input (McGuire et al 2010;Schneider et al 2012), and they also have a symbiotic relationship with aboveground vegetation, which benefits plant with more resistance against extreme circumstances like oligotrophic or arid habitats (Compant et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Rodrigues et al (2013), studying in pasture and forest in the Amazon showed a homogenization of microbial communities in response to human activities that was driven by the loss of forest soil bacteria and a net loss of diversity. Mueller et al (2014) sampled the soil microbial and plant community composition across a chronosequence of deforestation in the Amazon and found significant effects of landuse change on fungal community composition, which was more closely correlated to plant community composition than to changes in soil properties. Secondary forests had fungal communities more similar to primary forests than to those in pastures, which suggest that the recuperation of fungal communities after pasture abandonment is dependent upon that of plant diversity.…”
Section: Introductionmentioning
confidence: 99%